Full Silicon Tandem Solar Cells Based on Vertically Aligned Nanostructures - Dmitry A. Kudryashov; Ivan A. Morozov; Alexander S. Gudovskikh (International Journal of Photoenergy)
A three-dimensional computer simulation of flexible double-junction solar cells (SC) consisting of Si wires and p-i-n a-Si:H structures was carried out. The performance dependence on geometrical and electrical parameters was calculated. With an increase in the height of the Si wires, the open-circuit voltage (VOC) decreases monotonically for both the bottom Si and the top p-i-n a-Si:H junctions. The short-circuit current density (JSC) for the top p-i-n a-Si:H junction increases sharply with Si wire height, and then, it goes into saturation at a wire height of more than 10-15 μm. The absolute value of JSC increases (from 10.2 to 12.7 mA/cm2) with a decrease in the wire diameter (from 2 to 0.5 μm). For the bottom junction based on Si wires, the dependence of JSC on the wire height is determined by the charge carrier lifetime, doping level, and diameter, which can be associated with the effect of complete inversion of the Si wire conductivity type. For tandem SCs, the optimal wire height is 10 μm, at which efficiency of 14% can be achieved for structures based on Si wires with a diameter of 0.5 μm and a charge carrier lifetime of 10 μs. The practical implication of the developed design was experimentally demonstrated.